Multidimensional Scientometric Analysis for the Gig Economy - Sergen Gürsoy (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
The phenomenon of globalization, which gained momentum after the 1980s, became widespread in all parts of the society and research of working life has become a normal situation. The phenomenon of globalization has been included in the socio-economic structure of the society through internet networks. It is considered necessary for individuals to turn into an online business structure that emerges through digital platforms in order to continue their lives, to maintain welfare and peace. Thus, an increase in the trends of research on the structure of working life in terms of social sustainability in the changing world order has been observed. The aim of the study is to obtain a holistic perspective in the multidimensional areas of the Gig economy, which is the counterpart of the online working platform. For this purpose, all data (820/732) obtained from the Web of Science database specific to the gig economy were included in the research. Multiple data were analyzed using the CiteSpace application. Trends in the Gig economy within the framework of social network theory, analysis in the context of the country, author analysis, cluster analysis and representative document analysis are presented. In this context, it is important to be able to make scientometric analyzes within the scope of the literature on the gig economy in order to obtain systematic findings for future research on the current labor market. With the research, literature trends, country analyzes and relationship networks, author productivity and the interpretative equivalent of keywords in the literature are revealed. According to the analysis findings; For the gig economy phenomenon, researches have been carried out in different fields in the socio-economic structure, and it can be stated that the studies may increase cumulatively in the future in terms of its social importance and prevalence.